Positive electrode active material for rechargeable lithium ion battery

Through the specific heating and cooling process of positive electrode active materials with high Ni content, the molar ratio of material structure and Li/other metal elements is optimized, the problem of Ni2+ at the Li+ site is solved, LiOH impurities are reduced, and the electricity of lithium batteries is improved. Chemical properties and capacity stability.

CN119183441APending Publication Date: 2024-12-24UMICORE BATTERY MATERIALS CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042558.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-13
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Ni2+ exists at the Li+ site in the existing positive electrode active materials, resulting in high capacity attenuation during the cycle of lithium batteries, and LiOH impurities affect battery performance and are difficult to effectively reduce.

Method used

Using positive electrode active materials with high Ni content, the (003)/(104) peak intensity ratio in the X-ray diffraction pattern is controlled, and the crystal structure of the material and the molar of Li/other metal elements are optimized. The ratio reduces LiOH impurities and forms a polycrystalline particle-based powder.

Benefits of technology

It significantly improves the electrochemical performance of positive electrode active materials, reduces LiOH content, reduces post-treatment requirements, improves capacity attenuation rate, and achieves higher structural stability and performance optimization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183441A_ABST
    Figure CN119183441A_ABST
Patent Text Reader

Abstract

A positive electrode active material comprising lithium, a metal other than lithium, and oxygen, where the metal has a composition M, where M is composed of Ni in a content of x, Mn in a content of y, Co in a content of z, and A in a content of a, where x, y, z, and a are expressed as molar contents, where x + y + z + a = 100%, where x > = 70.0%, where 0 < = y < = 30.0%, where 0 < = z < = 30.0%, where 0 < = a < = 2.0%, where 0 < = a < = 2.0%, where 0 < = a < = 2.0%, where 0 < = z < = 30.0%, where 0 < = a < = 2.0%, where 0 < = a < = 2.0%, where 0 < = z < = 30.0%, where 0 < = a < = 2.0%, and wherein an X-ray diffraction pattern of the positive electrode active material has a (003) peak at 2 [theta] = 17.0 DEG to 20.0 DEG and a (104) peak at 2 [theta] = 43.0 DEG to 46.0 DEG, and wherein a ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at least 1.530.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a positive electrode active material, and more particularly to a positive electrode active material in which the metal has a high Ni content (generally, 70 mol % or more relative to the total transition metal content).

[0002] Such positive electrode active materials are known from KR20210018139 A.

[0003] Such positive electrode active materials should preferably have a well-ordered crystal structure. However, in practice, Ni 2+ Li can exist in the lattice + This, in turn, degrades battery performance, such as high capacity fade during cycling.

[0004] It is well known that the peak intensity ratio of the (003) / (104) peak in the XRD diffraction pattern can be used as a proxy for the degree of cation mixing (in other words, the Li + Ni on the site 2+ market share).

[0005] Such positive electrode active materials may be used as positive electrode active materials for Li-based batteries, but may also be considered as intermediate products that may undergo additional processing steps to improve their performance as positive electrode active materials.

[0006] The present invention aims to improve positive electrode active materials and thus provides a positive electrode active material for a lithium rechargeable battery, the positive electrode active material comprising lithium and a metal other than lithium and oxygen, wherein the metal has a composition M, wherein M is composed of Ni with a content of x, Mn with a content of y, Co with a content of z and A with a content of a, wherein A is at least one chemical element other than Li, Ni, Mn, Co and O, wherein x, y, z and a are expressed as molar contents, wherein x + y + z + a = 100 mol %,

[0007] Where x ≥ 70.0 mol%,

[0008] Where 0 mol% ≤ y ≤ 30.0 mol%,

[0009] Where 0 mol% ≤ z ≤ 30.0 mol%,

[0010] Where 0 mol%≤ a ≤ 5.0 mol%,

[0011] The positive electrode active material has an X-ray diffraction pattern obtained from a Cu K-α X-ray radiation source having a (003) peak located at 2θ = 17.0° to 20.0° and a (104) peak located at 2θ = 43.0° to 46.0°, wherein the ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at least 1.530.

[0012] The advantage is that such positive electrode active materials have better performance than known positive electrode active materials.

[0013] Preferably, x, y, z and a are measured by ICP-OES (Inductively Coupled Plasma).

[0014] Preferably, the positive electrode active material is a powder.

[0015] In one embodiment, element A is selected from the group consisting of Ag, Al, As, Au, B, Ba, Bi, Ca, Ce, Cd, Cr, Cs, Eu, Fe, Ga, Ge, Hg, Sb, Se, In, Ir, K, La, Mg, Mo, Na, Nb, Nd, Os, P, Pb, Pd, Pr, Pt, Rb, Re, Rh, Ru, S, Sc, Se, Si, Sm, Sr, Ta, Te, Ti, Y, V, W, Zn and Zr, or a combination thereof.

[0016] Preferably, element A is selected from the group consisting of Al, As, B, Ba, Ca, Ce, Cd, Cr, Cs, Fe, Ga, Ge, Se, In, Ir, K, Mg, Mo, Na, Nb, Nd, P, Pd, Pt, S, Sc, Se, Si, Sr, Ta, Te, Ti, Y, V, W, Zn and Zr or a combination thereof.

[0017] Even more preferably, element A is selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, Zn and Zr or combinations thereof.

[0018] In a preferred embodiment, the ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at least 1.540, and more preferably at least 1.550.

[0019] Therefore, the beneficial effects of the present invention exist to an even greater extent.

[0020] In a preferred embodiment, the molar ratio in the positive electrode active material: Li / (other metal elements except Li) is at least 0.90 and at most 1.10.

[0021] In a preferred embodiment, the positive electrode active material is represented by formula (1):

[0022] Li m Ni x Mn y Co z A a O2 formula (1),

[0023] wherein m is at least 0.90 and at most 1.10.

[0024] In a preferred embodiment:

[0025] ● x>80.0 mol %, preferably x>85.0 mol % and more preferably x>88.0 mol %; and / or

[0026] ● x < 98.5 mol % and preferably x < 97.0 mol %; and / or

[0027] ● y ≤ 20 mol % and preferably y ≤ 10 mol %; and / or

[0028] ● z ≤ 20 mol % and preferably z ≤ 10 mol %; and / or

[0029] ● (y+z)>1.0 mol % and preferably (y+z)>2.5 mol %; and / or

[0030] • y>0.5 mol % and z>0.5 mol %.

[0031] In a preferred embodiment, the positive electrode active material comprises LiOH in an amount of at most 1.40 wt %, more preferably at most 1.30 wt % and most preferably at most 1.20 wt % relative to the total weight of the positive electrode active material, wherein the content of LiOH is measured by acid-base (pH) titration as described in the specification.

[0032] LiOH impurities in the positive electrode active material significantly reduce the performance of the final battery and therefore need to be reduced as much as possible.

[0033] In a preferred embodiment, 0 mol % ≤ a ≤ 2.0 mol %.

[0034] Preferably, the positive electrode active material is a powder, in other words a plurality of particles.

[0035] More preferably, the positive electrode active material is a powder in which the majority of particles are polycrystalline particles. Such powders are also referred to as polycrystalline particle-based powders.

[0036] A particle is considered polycrystalline if it consists of 5 or more primary particles, preferably 10 or more primary particles, more preferably 50 or more primary particles (as observed in a SEM image). Figure 3 An example of a polycrystalline grain is shown in FIG.

[0037] The primary particles may also be referred to as grains, such that the primary particles may be distinguished from one another by observing grain boundaries.

[0038] In the SEM image of the positive electrode active material powder, at least 45 μm×at least 60 μm (i.e. at least 2700 μm 2 ), preferably at least 100µm x 100µm (ie at least 10,000µm 2 ) in a field of view, preferably at least 50%, more preferably at least 80% of the particles are polycrystalline.

[0039] The invention further relates to a first method for producing a positive electrode active material according to the invention, the first method comprising the following consecutive steps:

[0040] a) heating the precursor material at a heating temperature T1 between 750° C. and 1000° C., preferably between 800° C. and 950° C., and more preferably between 850° C. and 925° C., for a time period t1 between 2 hours and 20 hours, preferably between 3 hours and 15 hours, even more preferably between 4 hours and 10 hours, to obtain a heated product,

[0041] b) cooling the heated product to a second temperature T2 between 600°C and 800°C, preferably between 625°C and 775°C, even more preferably between 650°C and 750°C, and even more preferably between 675°C and 725°C, to obtain a second heated product, wherein the average cooling rate is between 10°C / h and 50°C / h, preferably between 20°C / h and 40°C / h, and more preferably between 25°C / h and 35°C / h, to obtain a first cooled product,

[0042] c) further cooling the first cooled product to obtain the positive electrode active material.

[0043] In a preferred variant of the first method, during step b, the heated product is subjected to a temperature reduction at an average rate of at most 45° C. / hour, preferably at most 35° C. / hour, over the duration of the second heat treatment step.

[0044] In a preferred variant of the first method, during the entire duration of step b, the heated product is subjected to a temperature that decreases over time or remains constant over time. Obviously, such a method can be carried out in an industrial furnace, where rapid temperature changes are not possible, so that these terms must be understood in the context of what is practical in an industrial scale furnace.

[0045] In one embodiment, the temperature of the process of the present invention is the set temperature of the furnace.

[0046] In a preferred variant of the first method, during at least a part of the duration of step b, and preferably during the entire duration of step b, the heated product is subjected to a temperature which decreases at a constant rate over time.

[0047] The present invention further relates to a second method for producing a positive electrode active material according to the present invention, the second method comprising the following consecutive steps:

[0048] a) heating the precursor material at a heating temperature T1 between 750° C. and 1000° C., preferably between 800° C. and 950° C., and more preferably between 850° C. and 925° C., for a time period t1 between 2 hours and 20 hours, preferably between 3 hours and 15 hours, even more preferably between 4 hours and 10 hours, to obtain a heated product,

[0049] b) cooling the heated product to a second temperature T2 between 650°C and 900°C, preferably between 700°C and 875°C, even more preferably between 750°C and 850°C, and even more preferably between 775°C and 825°C, and maintaining the temperature T2 for a time t2 between 5 hours and 20 hours, preferably between 7.5 hours and 17.5 hours, even more preferably between 10 hours and 15 hours, to obtain a first cooled product,

[0050] c) further cooling the first cooled product to obtain the positive electrode active material.

[0051] The present inventors have discovered that the cooling profile significantly improves the product characteristics and produces the positive electrode active material of the present invention.

[0052] The cooling characteristic diagram produces a positive electrode active material according to the present invention with a reduced LiOH content. Therefore, the positive electrode active material has better electrochemical performance. In addition, the positive electrode active material requires less post-treatment (such as washing) or no post-treatment.

[0053] Moreover, compared with the conventional method, no excess lithium source material is required or a lower excess lithium source material is required.

[0054] Furthermore, the method allows the production of positive electrode active materials, preferably positive electrode materials according to the invention.

[0055] The following preferred variations apply to both the first method and the second method.

[0056] In a preferred variant, x, y, z and a are measured by ICP-OES (Inductively Coupled Plasma).

[0057] In a preferred variant, ΔT, defined as T1 - T2, is between 20°C and 400°C, preferably between 50°C and 350°C.

[0058] In a preferred variant, x ≥ 80.0 mol %, more preferably x ≥ 85.0 mol % and even more preferably x ≥ 88.0 mol %.

[0059] In a preferred variant, x < 100.0 mol %, more preferably x < 98.5 mol % and even more preferably x < 97.0 mol %.

[0060] In a preferred variant, (y+z)>0 mol %, more preferably (y+z)>1.5 mol %, and even more preferably (y+z)>3.0 mol %.

[0061] In a preferred variant, x<97.0 mol % and y>1.0 mol % and z>1.0 mol %.

[0062] In a preferred variation, the positive electrode active material is a powder.

[0063] In a preferred variation, the molar ratio in the positive electrode active material: Li / (other metal elements than Li) is at least 0.90 and at most 1.10.

[0064] In a preferred variation, the precursor material comprises a source of M and a source of Li, preferably both in an oxidized state.

[0065] In a preferred variant, y ≤ 15.0 mol % and more preferably y ≤ 7.5 mol %.

[0066] In a preferred variant, z ≤ 15.0 mol %, and more preferably z ≤ 7.5 mol %.

[0067] In a preferred variant of the first method or the second method, the positive electrode active material is a positive electrode active material according to the invention.

[0068] In a preferred embodiment of the positive electrode active material according to the present invention, the positive electrode active material is produced by the method according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 An exemplary temperature characteristic diagram of EX1.1 according to the present invention is shown.

[0070] Figure 2 An exemplary temperature characteristic diagram of EX4.2 according to the present invention is shown.

[0071] Figure 3 Shown is a SEM image of CEX3 having a polycrystalline morphology.

[0072] Experimental Tests Used in the Examples

[0073] The following analytical methods were used in the examples:

[0074] A) Particle size distribution (PSD) analysis

[0075] After dispersing the examples of the positive electrode active material powders as described below in an aqueous medium, the PSD was measured using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory. In order to improve the dispersibility of the positive electrode active material powder examples, sufficient ultrasonic irradiation and stirring were applied, and appropriate surfactants were introduced. D50 was defined as the particle size at 50% of the cumulative volume % distribution.

[0076] B) Inductively coupled plasma optical emission analysis (ICP-OES) analysis

[0077] The positive electrode active material examples described below were measured using an Agillent ICP 720-OES by inductively coupled plasma emission spectrometry (ICP-OES) method. A 1 gram powder sample of each example was dissolved in 50 mL of high purity hydrochloric acid in a conical flask. The flask was covered with a watch glass and heated on a hot plate at 380°C until the sample was completely dissolved. After cooling to room temperature, the solution and rinse water in the conical flask were transferred to a 250 mL volumetric flask. Afterwards, the volumetric flask was filled with deionized water until the 250 mL mark and then completely homogenized. An appropriate amount of solution was taken out by pipette and transferred to a 250 mL volumetric flask for the second dilution, at which time the internal standard and 10% hydrochloric acid were filled in the volumetric flask until the 250 mL mark and then homogenized. Finally, the solution was used for ICP-OES measurement. The contents of Ni, Mn, and Co are expressed as molar % of the total amount of these contents.

[0078] C) Button battery test

[0079] C1. Button Cell Preparation

[0080] To prepare the positive electrode, a slurry (in a formulation of 96.5:1.5:2.0 by weight) containing positive electrode active material powder, conductor (Super P, Timcal), binder (KF#9305, Kureha) was prepared by a high-speed homogenizer in a solvent (NMP, Mitsubishi). The homogenized slurry was applied to one side of the aluminum foil using a doctor blade coater with a gap of 170 μm. The slurry-coated foil was dried in an oven at 120°C and then pressed using a calendering tool. It was then dried again in a vacuum oven to completely remove the remaining solvent in the electrode film. The button cell was assembled in an argon-filled glove box. The separator (Celgard 2320) was located between the positive electrode and the lithium foil used as the negative electrode. EC / DMC (1:2) containing 1M LiPF6 was used as the electrolyte and was dripped between the separator and the electrode. Then, the button cell was completely sealed to prevent electrolyte leakage.

[0081] C2.Testing Methods

[0082] The test method was a conventional "constant cut-off voltage" test. The conventional button cell test in the present invention followed the schedule shown in Table 1. Each cell was cycled at 25°C using a Toscat-3100 computer controlled constant current cycling station (from Toyo).

[0083] A 1C current definition of 220 mA / g is planned to be used in the 4.3 V to 3.0 V / Li metal window range. The capacity fade rate (QF) is obtained according to the following equation.

[0084]

[0085] Where DQ1 is the discharge capacity of the first cycle, DQ7 is the discharge capacity of the 7th cycle, and DQ34 is the discharge capacity of the 34th cycle.

[0086] Table 1. Cycle schedule for coin cell battery test method

[0087]

[0088] D) Surface Alkali Analysis

[0089] In the measurement of soluble base content by pH titration, two steps are performed: (a) solution preparation, and (b) pH titration. A detailed explanation of each step is as follows:

[0090] Step (a): Preparation of solution: The powder was immersed in deionized water and stirred in a sealed glass flask containing 100 ml of deionized water for 10 min. The amount of positive electrode active material powder was 4 grams. After stirring to dissolve the base, the suspension of the powder in water was filtered to obtain a clear solution.

[0091] Step (b): pH titration: 90 ml of the clear solution prepared in step (a) was used for pH titration using 0.1 M HCl. The flow rate was 0.5 ml / min and the pH value was recorded every 3 seconds. The pH titration profile (pH as a function of added HCl) shows two clear equivalence (or turning) points. The first equivalence point at about pH 7.4 (corresponding to the amount of HCl in EP1) is determined by OH - and CO3 2- With H + The second equivalence point at about pH 4.7 (corresponding to the amount of HCl in EP2) is produced by HCO3 - With H + The base dissolved in the deionized water is assumed to be LiOH (in which the amount is 2*EP1-EP2) or Li2CO3 (in which the amount is 2*(EP2-EP1)). The values ​​obtained for LiOH and Li2CO3 are the result of the reaction of the surface with the deionized water.

[0092] E) X-ray powder diffraction (XRD)

[0093] E1) XRD measurement

[0094] X-ray diffraction patterns of the positive electrode active material powder examples described below were collected using a Rigaku X-ray diffractometer Ultima 4 using a Cu Kα radiation source (40 kV, 40 mA) emitting at a wavelength of 1.5418 Å. The instrument configuration was set to: 1° Sollerslit (SS), 10 mm divergence height limiting slit (DHLS), 1° divergence slit (DS), and 0.3 mm receiving slit (RS). The diameter of the goniometer was 185 mm. For XRD, diffraction patterns were obtained in the range of 15° to 50° (2θ) at a scan speed of 3° / min and a step size of 0.02° / scan.

[0095] E2) X-ray diffraction pattern analysis

[0096] The diffraction pattern obtained from E1) was analyzed in Origin 2018b version b9.5.5.409 according to the following steps:

[0097] 1. Endpoint weighted mode and 10% endpoint minus baseline

[0098] 2. Nonlinear curve fitting was performed using Voigt lines, one for each of the peaks located at 2θ between 17.0° and 20.0° for the (003) peak and 43.0° and 46.0° for the (104) peak. The Voigt line shape is according to the following equation:

[0099]

[0100] 3. From the obtained fitting curves, identify the maximum y-values, one each for the (003) and (104) peaks. The intensity ratio (003) / (104) is obtained by dividing the maximum y-value of the (003) peak by the maximum y-value of the (104) peak.

[0101] F) Scanning electron microscopy (SEM) analysis

[0102] The morphology of the positive electrode active material can also be performed by scanning electron microscopy (SEM) with a benchtop apparatus JEOL JCM-6100Plus. Example

[0103] The present invention is further illustrated in the following examples:

[0104] Comparative Example 1

[0105] The positive electrode active material CEX1.1 is prepared by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0106] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.90 Mn 0.05 Co 0.05 Transition metal oxide hydroxide precursors.

[0107] 2. Mixing: The precursor prepared from step 1) was mixed with LiOH and ZrO2 in an industrial blender to obtain a mixture containing 0.25 mol% Zr and having a lithium to metal ratio of 1.02.

[0108] 3. Heating: The mixture from step 2) was heated under a flow of oxygen at a first temperature of 700° C. for a first duration of 10 hours, and then the temperature was increased to a second temperature of 840° C. for a second duration of 10 hours.

[0109] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain the positive electrode active material CEX1.1.

[0110] CEX1.2 was prepared according to the same method as CEX1.1, except that the first temperature was 840°C and the first duration was 10 hours, and then the temperature was reduced to a second temperature of 700°C for a second duration of 2 hours. CEX1.2 is according to prior art KR20210018139 A.

[0111] Example 1

[0112] EX1.1 was prepared according to the same method as CEX1.2, except that the second duration was 10 hours.

[0113] EX1.2 was prepared according to the same method as CEX1.2, except that the second duration was 5 hours.

[0114] EX1.3 was prepared according to the same method as CEX1.2, except that the first duration was 5 hours and the second duration was 10 hours.

[0115] EX1.4 was prepared according to the same method as CEX1.2, except that the first duration was 5 hours and the second duration was 5 hours.

[0116] EX1.5 was prepared according to the same method as CEX1.2, except that the second temperature was 660° C. and the second duration was 10 hours.

[0117] EX1.6 was prepared according to the same method as CEX1.2, except that the second temperature was 740° C. and the second duration was 10 hours.

[0118] EX1.7 was prepared according to the same method as CEX1.2, except that the second temperature was 760° C. and the second duration was 10 hours.

[0119] EX1.8 was prepared according to the same method as CEX1.2, except that the second temperature was 660° C. and the second duration was 5 hours.

[0120] EX1.9 was prepared according to the same method as CEX1.2, except that the second temperature was 740° C. and the second duration was 5 hours.

[0121] EX1.10 was prepared according to the same method as CEX1.2, except that the second temperature was 760° C. and the second duration was 5 hours.

[0122] Comparative Example 2

[0123] The positive electrode active material CEX2 is obtained by a solid-state reaction between a lithium source and a transition metal-based source precursor in the following method steps:

[0124] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.92 Mn 0.03 Co 0.05 Transition metal based oxyhydroxide precursors.

[0125] 2. Mixing: The precursor prepared from step 1) and LiOH as a lithium source were uniformly blended in an industrial blending equipment at a lithium to metal M (Li / M) ratio of 0.99.

[0126] 3. Heating: The mixture obtained in step 2) was heated at 820°C for 10 hours under an oxygen gas flow.

[0127] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain CEX2.

[0128] Example 2

[0129] EX2 was prepared according to the same method as CEX2, except that step 3) was heated at a first temperature of 820°C for a first duration of 10 hours, and then the temperature was reduced to a second temperature of 700°C for a second duration of 5 hours.

[0130] Example 3

[0131] The positive electrode active material EX3 is prepared by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0132] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.94 Mn 0.03 Co 0.03 Transition metal oxide hydroxide precursors.

[0133] 2. Mixing: The precursor prepared from step 1) was mixed with LiOH, ZrO2, Al2O3 in an industrial blender to obtain a mixture containing 1500 ppm Zr and 700 ppm Al relative to the total weight of Ni, Mn and Co and having a lithium to metal ratio of 0.95.

[0134] 3. Heating: The mixture from step 2) was heated at a first temperature of 830° C. for 10 hours under a stream of oxygen gas, and then the temperature was reduced to a second temperature of 710° C. for 10 hours.

[0135] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain positive electrode active material EX3.

[0136] Example 4

[0137] The positive electrode active material EX4.1 is prepared by a solid state reaction between a lithium source and a transition metal based source precursor according to the following steps:

[0138] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.88 Mn 0.05 Co 0.07 Transition metal oxide hydroxide precursors.

[0139] 2. Mixing: The precursor prepared from step 1) was mixed with LiOH and ZrO2 in an industrial blender to obtain a mixture containing 0.25 mol% Zr relative to the total molar content of Ni, Mn and Co and having a lithium to metal ratio of 0.98.

[0140] 3. Heating: The mixture from step 2) was heated at a first temperature of 880° C. for 5 hours under a flow of oxygen, and then the temperature was reduced to a second temperature of 760° C. for 7.5 hours.

[0141] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain positive electrode active material EX4.1.

[0142] EX4.2 was prepared according to the same method as EX4.1, except that after the first heating at 880°C, the temperature was slowly decreased to 700°C at a rate of 30°C / hour, and then cooled to room temperature.

[0143] Comparative Example 3

[0144] The positive electrode active material CEX3 is obtained by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0145] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.90 Mn 0.05 Co 0.05 Transition metal oxide hydroxide precursors.

[0146] 2. First mixing: The precursor prepared from step 1) was mixed with LiOH in an industrial blender to obtain a mixture having a lithium to metal ratio of 1.06.

[0147] 3. Heating: The first mixture from step 2) was heated at 890° C. for 10 h under a stream of oxygen.

[0148] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain the positive electrode active material CEX3.1.

[0149] 5. Wet bead milling: CEX3.1 was bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn and Co in the first heated product, followed by a drying and sieving process to obtain a ground product. The bead milling solid to solution weight ratio was 6:4 and was performed for 20 minutes.

[0150] 6. Second mixing: The ground product from step 4) was mixed with H3BO3 as a B source and WO3 as a W source to obtain a third mixture containing 250 ppm B and 2000 ppm W.

[0151] 7. Heat treatment: The second mixture from step 5) was heated at 350° C. for 7 hours under an oxygen atmosphere to obtain CEX3.2 comprising Ni, Mn and Co in a ratio Ni:Mn:Co of 0.89:0.05:0.06 as measured by ICP-OES. CEX3.2 had a D50 of 4 μm.

[0152] Example 5

[0153] The positive electrode active material EX5 is obtained by a solid-state reaction between a lithium source and a transition metal-based source precursor according to the following steps:

[0154] 1. Coprecipitation: A coprecipitation process was used to prepare a metal composition of Ni in a large continuous stirred tank reactor (CSTR) with mixed nickel-manganese-cobalt sulfate, sodium hydroxide and ammonia. 0.90 Mn 0.05 Co 0.05 Transition metal oxide hydroxide precursors.

[0155] 2. First mixing: The precursor prepared from step 1) was mixed with LiOH and ZrO2 in an industrial blender to obtain a mixture containing 0.125 mol% Zr and having a lithium to metal ratio of 1.02.

[0156] 3. Heating: The first mixture from step 2) was heated at a first temperature of 870° C. for 10 hours under a flow of oxygen, and then the temperature was reduced to a second temperature of 700° C. and kept constant for 10 hours.

[0157] 4. Post-treatment: The heated powder from step 3) was crushed and sieved to obtain positive electrode active material EX5.1.

[0158] 5. Wet bead milling: The heated product from step 3) was bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn and Co in the first heated product, followed by a drying and sieving process to obtain a ground product. The bead milling solid to solution weight ratio was 6:4 and was performed for 20 minutes.

[0159] 6. Second mixing: The ground product from step 4) was mixed with H3BO3 as a B source and WO3 as a W source to obtain a third mixture containing 125 ppm B and 1000 ppm W.

[0160] 7. Heat treatment: The second mixture from step 5) was heated at 350°C for 7 hours under an oxygen atmosphere to obtain EX5.2, which contained Ni, Mn and Co in a ratio Ni:Mn:Co of 0.89:0.05:0.05 as measured by ICP-OES. EX5.2 had a D50 of 4 µm.

[0161] result

[0162] The results of experimental tests for the embodiments described above are as follows:

[0163] Table 2. Heating conditions and characteristics of positive electrode active materials CEX1.1, CEX1.2, CEX2, EX1.1 to EX1.10, EX2, EX3, EX4.1 and EX4.2

[0164]

[0165] n / a = not applicable

[0166] Table 3. Characteristics of positive electrode active materials CEX3 and EX3

[0167]

[0168] Table 2 summarizes the heating conditions, compositions and XRD peak analysis of the Examples and Comparative Examples.

[0169] Compared with EX1.1 to EX1.10, which are positive electrode active materials containing the same amount of Ni, CEX1.1, which was prepared without the second heat treatment at a reduced temperature, contains a higher amount of LiOH. In addition, XRD diffraction pattern analysis shows that the peak intensity ratio (003) / (104) of EX1.1 to EX1.10 exceeds 1.53, wherein the maximum intensity of the peak (003) is located at 2θ between 17.0° and 20.0° and the maximum intensity of the peak (104) is located at 2θ between 43.0° and 46.0°. The intensity ratio of (003) / (104) indicates the degree of structural disorder, wherein a lower ratio shows a higher structural disorder caused by cation mixing between Li atoms and Ni atoms. In addition, CEX1.2 prepared with a short t2 of 2 hours shows 1.43 wt% of LiOH base, which indicates that sufficient time is required at the second temperature to alleviate both the structural disorder problem and the surface base problem.

[0170] EX1.1 to EX1.4 were prepared, where the variation of t1 and t2 showed that a t2 of 10 hours was beneficial for reducing LiOH. On the other hand, an extended t2 was associated with a lower furnace throughput. EX1.5 to EX1.10 were prepared positive electrode active materials where the time period of the second heating was changed to 5 hours to 10 hours. A comparison of ΔT in the range of 50°C to 300°C was shown to be necessary to reduce LiOH impurities.

[0171] CEX2 and EX2 are positive electrode active materials containing about 92 mol % Ni, which were prepared without and with a second heat treatment at a reduced temperature, respectively. This comparison shows that applying a second heat treatment at a reduced temperature reduces the LiOH base and maintains a (003) / (104) XRD peak ratio above 1.53.

[0172] CEX3.1 and EX5.1 are positive electrode active materials containing about 89 mol% Ni, which were prepared without and with a second heat treatment at a reduced temperature, respectively. This comparison shows that applying a second heat treatment at a reduced temperature reduces the LiOH base and maintains the (003) / (104) XRD peak ratio above 1.53.

[0173] Table 3 summarizes the heating conditions, composition, XRD peak analysis and electrochemical characteristics of CEX3 and EX5. CEX3 and EX5 are positive electrode active materials, which are prepared without and with the second heat treatment, respectively. This comparison shows that applying the second heat treatment reduces the LiOH base and keeps the (003) / (104) XRD peak ratio above 1.88. In addition, compared with CEX3, the capacity decay QF of EX5 is significantly improved.

Claims

1. A positive electrode active material comprising lithium and a metal other than lithium and oxygen, wherein the metal has a composition M, wherein M is composed of Ni in an amount x, Mn in an amount y, Co in an amount z, and A in an amount a, wherein A is at least one chemical element other than Li, Ni, Mn, Co, and O, wherein x, y, z, and a are expressed as molar contents, wherein x + y + z + a = 100 mol %. Where x ≥ 70.0 mol%, Where 0 mol% ≤ y ≤ 30.0 mol%, Where 0 mol% ≤ z ≤ 30.0 mol%, Where 0 mol% ≤ a ≤ 5.0 mol%, wherein the positive electrode active material has an X-ray diffraction pattern obtained from a Cu K-α X-ray radiation source having a (003) peak located at 2θ from 17.0° to 20.0° and a (104) peak located at 2θ from 43.0° to 46.0°, wherein the ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at least 1.530, The positive electrode active material comprises LiOH in an amount of up to 1.40 wt % relative to the total weight of the positive electrode active material, wherein the content of LiOH is measured by acid-base titration. 2 . The positive electrode active material according to claim 1 , wherein the ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at least 1.

550. 3 . The positive electrode active material according to claim 1 , wherein the ratio (maximum intensity of the (003) peak) / (maximum intensity of the (104) peak) is at most 3.

000. 4 . The positive electrode active material according to claim 1 , wherein the molar ratio of Li / (metal elements other than Li) in the positive electrode active material is at least 0.90 and at most 1.

10.

5. The positive electrode active material according to any one of the preceding claims, wherein the positive electrode active material is represented by formula (1): Li m Ni x Mn y Co z A a O₂ of formula (1), wherein m is at least 0.90 and at most 1.

10.

6. A positive electrode active material according to any one of the preceding claims, wherein x>85.0 mol %.

7. A positive electrode active material according to any one of the preceding claims, wherein x>88.0 mol %.

8. A positive electrode active material according to any one of the preceding claims, wherein x < 98.5 mol %.

9. The positive electrode active material according to any one of the preceding claims, wherein (y+z) > 1.0 mol %.

10. The positive electrode active material according to any one of the preceding claims, wherein y>0.5 mol% and wherein z>0.5 mol%.

11. The positive electrode active material according to any one of the preceding claims, wherein the positive electrode active material comprises LiOH in an amount of up to 1.30 wt. % relative to the total weight of the positive electrode active material, wherein the LiOH content is measured by acid-base titration.

12. The positive electrode active material according to any one of the preceding claims, wherein the positive electrode active material comprises LiOH in an amount of up to 1.20 wt. % relative to the total weight of the positive electrode active material, wherein the LiOH content is measured by acid-base titration.

13. The positive electrode active material according to any one of the preceding claims, wherein the positive electrode active material is polycrystalline.

14. A method for producing a positive electrode active material according to any one of the preceding claims, the method comprising the following consecutive steps: a) heating a precursor material comprising an M source and a Li source at a heating temperature T1 between 750° C. and 1000° C., preferably between 800° C. and 950° C., and more preferably between 850° C. and 925° C., for a time period t1 between 2 hours and 20 hours, preferably between 3 hours and 15 hours, and even more preferably between 4 hours and 10 hours, to obtain a heated product, b) cooling the heated product to a second temperature T2 to obtain a first cooled product, c) further cooling the first cooled product to obtain the positive electrode active material, wherein step b is: cooling the heated product to a second temperature T2 between 600°C and 800°C, preferably between 625°C and 775°C, even more preferably between 650°C and 750°C, and even more preferably between 675°C and 725°C, to obtain a second heated product, wherein the average cooling rate is between 10°C / h and 50°C / h, preferably between 20°C / h and 40°C / h, and more preferably between 25°C / h and 35°C / h, Or wherein step b is: cooling the heated product to a second temperature T2 between 650°C and 900°C, preferably between 700°C and 875°C, even more preferably between 750°C and 850°C, and even more preferably between 775°C and 825°C, and maintaining the temperature T2 for a time t2 between 5 hours and 20 hours, preferably between 7.5 hours and 17.5 hours, even more preferably between 10 hours and 15 hours.

15. The method according to claim 14, wherein ΔT = (T1-T2), wherein 20°C ≤ ΔT ≤ 400°C, preferably 50°C ≤ ΔT ≤ 350°C, more preferably wherein 300°C ≤ T3 ≤ 800°C.